PENOLAKAN ITSBAT NIKAH DI MASA PANDEMI COVID-19 MENURUT KOMPILASI HUKUM ISLAM (STUDI PUTUSAN NOM0R 47/Pdt.P/2021/Pa.Tas) - Andika Setya Amanullah; Muriani (Faculty of Law, Universitas Trisakti, 2023)
The widespread spread of the COVID-19 pandemic in Indonesia has caused the government to limit various community activities, one of which is holding weddings. Therefore, there are many married couples who carry out their marriages using sirhi, but in this case, can a husband and wife whose marriage is sirhi submit their marriage contract to the Religious Court? The main issue is what factors led to the rejection of the Religious Court's application for itsbat marriage and whether Decision Number 47/Pdt.P/2021/Pa.Tas regarding the rejection of the itsbat decision was in accordance with the Complications of Islamic Law. The type of research used is normative juridical using secondary data obtained through literature study. The results of the research show that there are factors causing the rejection of marriage licenses by the Religious Courts, and Decision Number 47/Pdt.P/ 2021 /Pa.Tas in this case is not in accordance with the Complications of Islamic Law, because marriages are carried out in pairs without any obstacles to marriage. In conclusion, the application for marriage itsbat can be rejected by the religious court if it does not comply with the provisions of Article 7 paragraph (3) of the Compilation of Islamic Law.